Structural and electrical characterisation of PtS from H2S-converted Pt. (December 2021) - Monaghan, Scott; Coleman, Emma M.; Ansari, Lida; Lin, Jun; Buttimer, Alexandra; Coleman, Patrick A.; Connolly, James; Povey, Ian M.; Kelleher, Bryan; Ó Coileáin, Cormac; McEvoy, Niall; Hurley, Paul K.; et al.
Highlights: First report of the electrical characteristics of polycrystalline PtS as a thin uniform semiconductor film, encompassing resistance and Hall-effect measurements as well as back-gated junctionless MOSFET measurements with complementary simulations. First report of structural characterisation of a polycrystalline PtS film with high-resolution cross-sectional transmission electron microscopy (HR-XTEM). Manufacturing-compatible process for Pt to PtS formation by thermal conversion in a gaseous H2 S + H2 atmosphere with a uniform sulfur supply to the Pt surface in a 300 mm-chamber reactor designed for atomic layer deposition or chemical vapour deposition, ideal for 3D integration of materials and devices with CMOS in Beyond-CMOS and More-than-Moore technologies. Advanced commercial-grade Sentaurus TCAD software in first-pass approximation simulations of PtS provide support to the PtS experimental observations with excellent fitting to experimental measurements. First report of electronic structure calculations and the dielectric constant of PtS beyond the generalised Density-Functional Theory level. The Heyd-Scuseria-Ernzerhof (HSE) hybrid functional is included in the model to provide a more accurate prediction of the PtS band gap, which if realised experimentally, may suggest a lower off-current and a larger Ion /Ioff ratio for PtS Metal-Oxide-Semiconductor Field-Effect Transistors (MOSFETs). Abstract: A manufacturing-compatible 300 mm chamber reactor for atomic layer deposition or chemical vapour deposition, and pre-fitted with H2 /H2 S gases that can be uniformly delivered to the wafer surface, is employed to thermally convert Pt to PtS in a H2 /H2 S gaseous atmosphere for 7 hours at a chamber temperature of 550 °C. Prior to conversion, platinum layers 5 nm thick are uniformly deposited by electron beam evaporation onto ∼30 nm of amorphous aluminium sesquioxide deposited by atomic layer deposition on, (a) p -type silicon, and (b) c-plane sapphire. Structural characterisation is performed by high-resolution cross-sectional transmission-electron microscopy, scanning-electron microscopy and Raman spectroscopy, confirming the formation of continuous films of polycrystalline platinum monosulfide (PtS) with a ∼15 nm thickness. Electrical characterisation is performed by 4-point resistivity and Hall-effect transport measurements on van der Pauw structures of PtS on aluminium sesquioxide on c-plane sapphire, and by back-gate junctionless MOSFET device measurements for PtS on aluminium sesquioxide on p -type silicon, showing that PtS behaves as a semiconductor with a mobility of ∼16 cm 2 /V.s and with an n -type carrier concentration of ∼1.2 × 10 15 cm −3 . Advanced commercial-grade Sentaurus simulations, alongside density-functional theory calculations, agree well with the experimental observations and suggest a large bandgap of ∼1.58 eV may be possible that could lead to a low off-current and a high Ion /Ioff ratio, suggesting that PtS may be an advanced material candidate for future device integration with CMOS and for 3D integration applications in Beyond-CMOS and More-than-Moore technologies. Graphical abstract: Image, graphical abstract